2015
DOI: 10.1084/jem.20142274
|View full text |Cite
|
Sign up to set email alerts
|

Functional IRF3 deficiency in a patient with herpes simplex encephalitis

Abstract: Andersen et al. identify a novel genetic etiology of herpes encephalitis in an adult patient carrying a heterozygous loss-of-function mutation in the IRF3 gene. This mutation results in impaired INF production in response to viral infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
146
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(159 citation statements)
references
References 29 publications
10
146
1
2
Order By: Relevance
“…These findings were supported by subsequent analysis of patients with defects in genes encoding the TLR3 signalling components TRIF, TBK-1 and IRF3 [35][36][37]. An impaired TLR3-inducible type-1 IFN response to HSV-1 in neurons and oligodendrocytes in the central nervous system (CNS) was subsequently linked with this condition [32][33][34][35][36][37]. These findings are also consistent with studies in mouse models of DNA virus infections.…”
Section: Role Of Tlr3 In Host Defencesupporting
confidence: 66%
“…These findings were supported by subsequent analysis of patients with defects in genes encoding the TLR3 signalling components TRIF, TBK-1 and IRF3 [35][36][37]. An impaired TLR3-inducible type-1 IFN response to HSV-1 in neurons and oligodendrocytes in the central nervous system (CNS) was subsequently linked with this condition [32][33][34][35][36][37]. These findings are also consistent with studies in mouse models of DNA virus infections.…”
Section: Role Of Tlr3 In Host Defencesupporting
confidence: 66%
“…With respect to RNA virus infections, all 4 patients' cells responded with normal expression of type I and III IFNs to all viruses tested (Figure 5, F and G). Examination of the induction of IFNA2 and IFNL1 in cells from patients carrying mutations previously shown to confer susceptibility to HSE revealed that only IRF3 deficiency, but not TLR3 or TRIF deficiency, conferred reduced VZV-stimulated IFN expression (Supplemental Figure 13, A and B) (17,18,22). This IRF3 defect also ablated induction of IFNL1 by HSV-1 but did not affect the response to influenza A (IAV) infection (Supplemental Figure 13, C and D).…”
Section: Induction Of Ifns By At-rich Dna In Human Pbmcs Is Pol Iii-dmentioning
confidence: 91%
“…A striking example is that mutations in genes controlling Toll-like receptor (TLR) 3-dependent type I and III IFN-mediated immunity confer susceptibility to herpes simplex encephalitis (HSE) (17)(18)(19)(20)(21)(22). Notably, these genetic defects often appear to display incomplete penetrance, in which case they can be designated as monogenic but not Mendelian (18,20,23).…”
Section: Identification Of Heterozygous Mutations In Polr3a and Polr3mentioning
confidence: 99%
“…We analyzed genome-wide linkage data and both blood and fibroblastic responses to herpes simplex virus and various viral intermediates in children with isolated HSE from this IFN-α/β-based angle, and we discovered mutations affecting five genes governing the TLR3-mediated IFN-α/β pathway (116)(117)(118)(119)(120)(121). Another group recently identified a mutation in a sixth gene (122). TLR3 can recognize viral dsRNA intermediates.…”
Section: Hse: a Genetic Diseasementioning
confidence: 99%